Continuous intention criteria of sns appropriation process in family context: A systematic literature review - Mahmud, Yuzi (Penerbit UTM Press, 2015)
Communication technologies such as Social Network Sites (SNSs) are increasingly being used within family settings to support and extend the family relationships. Although many previous researchers have highlighted the impact of SNSs in family environment, criteria of SNS adoption and use in family context have received little research attention. This paper highlights selected SNS appropriation process criteria in family, individual and technical perspectives in order to understand why and how the SNS is being used in family context. Using the procedure of Bandara et al. (2011), NVivo 9.0 was employed to conduct content analysis of 284 articles published between the year of 2006 until 2014. As a result, the adoption and use criteria of SNS appropriation process were identified, and has been categorized in family, individual and technical perspectives using the Family Appropriation Process of Social Network Site (FAPSNS) framework. The understanding of the criteria could assist in effective and healthy adoption and use of SNSs among family members. However, this paper is merely focusing on level 2 and level 3 of SNS appropriation process in family, individual and technical perspectives.